Pengaruh Kompetensi Jawatan dan Pembangunan Kerjaya Staf Terhadap Prestasi Kerja di Pejabat Pemerintah Daerah Kabupaten Tana Toraja - Bernadeth Tongli; Ishak Bin Mad Shah (Jurnal Dinamika Pendidikan dan Pembelajaran, 2015)
This research takes as its focus the major problem of low employee performance at the Government Office of Tana Toraja Regency. The cause of this problem is thought to be the non- implementation of Job Competency and Employee Career Development on Employee Performance at the Government Office of Tana Toraja Regency. The approach taken in this research refers to the context of the Job Competency and Employee Career Development theory, as part of the scope of the Science of Public Administration through the use of the research method of explanatory  survey  Dan  Structural  Equation  Modeling  (SEM),  whereas  population  is  the Government Office of Tana Toraja Regency. The result of the research shows the need for the undertaking of  further  research  regarding  the  need  to  optimize the  improvement of  the influence of Job Competency and Employee Career Development on Employee Performance at the Government Office of Tana Toraja Regency, as seen from the perspective of Public Administration. This is shown by the existence of different variables which influence the Employee Performance at the Government Office of Tana Toraja Regency.